2013
DOI: 10.1017/s1368980013002346
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for childhood overweight: a 30-month longitudinal study of 3- to 6-year-old children

Abstract: Objective: The increasing prevalence of childhood overweight is an important health issue. There is a need for longitudinal research among children in order to identify risk factors for childhood overweight. The objective of the present research was to identify potential sociodemographic and behavioural risk factors for development of childhood overweight among 3-to 6-year-old children. Design: Longitudinal study. Setting: Sixteen pre-primary and primary schools. Subjects: BMI Z-scores at baseline and two foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 53 publications
2
40
1
Order By: Relevance
“…Prospective studies including consumption of EDF other than SSB by younger children are particularly scarce [32,45,48] and, similarly to the present study results, Eur J Nutr found no association between EDF consumption and weight status. However, in older children, distinct results have been reported.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Prospective studies including consumption of EDF other than SSB by younger children are particularly scarce [32,45,48] and, similarly to the present study results, Eur J Nutr found no association between EDF consumption and weight status. However, in older children, distinct results have been reported.…”
Section: Discussionsupporting
confidence: 86%
“…Results from a study in the USA [40] give strength to the possibility of a low frequency of exposure, as levels of SSB consumption were also lower and no association with weight change was found. The higher prevalence of overweight and obesity in studies conducted in the USA [45,49,50], as well as in a study in the UK [30], may also explain the different results as the prevalence of overweight (including obesity) was much lower in our sample (8.6 % at 2 and 9.0 % at 4 years of age).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Firstly, the test group was selected from one area of South-Africa and the generalisability of the findings is therefore limited. Secondly, the limited ability of children and adolescents to respond to self-report questionnaires with regard to physical activity is widely recognised in literature (De Coen et al 2014;Chen et al 2014;Hnatiuk, Salmon, Hinkley, Okely, & Trost, 2014) and could have affected the results. However, the results of this study emphasise that motor proficiency and the mastery of fundamental movement skills have an important role to play, even in adolescent learners in the Senior Phase, with regard to current, but also future participation in physical activity.…”
mentioning
confidence: 99%
“…Unadjusted associations were reported by De Coen et al They found that children of overweight mothers were 2.99 times (95% CI: 1.80-4.97) more likely to become overweight at 5 years old compared to children of normal weight mothers [110]. They also reported however, that there was no significant increased risk of being overweight among children of an overweight father.…”
Section: Prenatal Parental -Offspring Bmi and Obesity Associationmentioning
confidence: 86%